A Novel Immunochromatographic Strip Based on Latex Microspheres for the Rapid Detection of North American-Type Porcine Reproductive and Respiratory Syndrome Virus - Li, Wansheng; Li, Minhua; Zhang, Hongliang; Li, Chao; Xu, Hu; Gong, Bangjun; Fu, Jun; Guo, Zhenyang; Peng, Jinmei; Zhou, Guohui; Tian, Zhijun; Wang, Qian (Frontiers in Microbiology, 2022)
A latex microsphere-based immunochromatographic strip (ICS) test was successfully developed for the rapid and sensitive detection of porcine reproductive and respiratory syndrome virus (PRRSV). The PRRSV N protein-specific monoclonal antibody (mAb) 1H4 labeled with latex microspheres was dispensed on a conjugate pad for use as the detector. The same mAb and goat anti-mouse antibody were blotted on a nitrocellulose membrane to generate test and control lines, respectively. The limit of virus detection was approximately 5 × 102.0 median tissue culture infectious dose (TCID50)/ml, and the limit of N protein detection was approximately 15 ng/ml. Other common porcine viruses were tested to evaluate the specificity of the ICS, and positive results were observed for only North American-type PRRSV. A comparison of the strip with a standard diagnostic test (reverse transcriptase polymerase chain reaction, RT-PCR) was also performed, and the results showed that the ICS test exhibited relatively high specificity and sensitivity (90.32 and 73.91%, respectively) and relatively high positive predictive value (PPV) and negative predictive value (NPV; 85 and 82.35%, respectively). These results suggest that the ICS test can be used to rapidly and accurately detect PRRSV and can be suitable for diagnostic applications in the field.